2015
DOI: 10.1097/sap.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of EMLA Cream and Ethyl Chloride Spray Application for Pain Relief of Forehead Botulinum Toxin Injection

Abstract: Skin cooling with ethyl chloride spray significantly decreases the pain associated during forehead botulinum toxin injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Skin cooling (with ethylchloride spray, dry cold, or ice) or local application of anesthetic cream decreases pain associated with limb or facial botulinum injections ( 81 83 ). As such, they may be beneficial in patients for the treatment of CD too, although no specific studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…Skin cooling (with ethylchloride spray, dry cold, or ice) or local application of anesthetic cream decreases pain associated with limb or facial botulinum injections ( 81 83 ). As such, they may be beneficial in patients for the treatment of CD too, although no specific studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…For example, France et al 16 showed that pain from arterial punctures was not affected using ethyl chloride coolant vapor. But Irkoren et al 17 showed that skin cooling with ethyl chloride spray significantly decreases the pain associated during forehead BTX injections. Moreover, crushed ice packs provide more effective cryoanalgesia than cold gel packs or cold water immersion.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl chloride spray is a cryoanaesthetic agent that fulfils many properties of an ideal topical anaesthetic: its onset is immediate, it is non‐invasive, it is effective, its offset is rapid and, in addition to these, it is low cost. Ethyl chloride spray is readily available in most hospital anaesthesia departments and has been demonstrated to be valuable as a topical anaesthetic in a range of paediatric and adult environments . Therefore it seemed appropriate to apply it in an attempt to minimise the discomfort from finger prick blood testing.…”
Section: Discussionmentioning
confidence: 99%